2003
DOI: 10.1128/jvi.77.16.8712-8718.2003
|View full text |Cite
|
Sign up to set email alerts
|

Replication-Competent Bacterial Artificial Chromosomes of Marek's Disease Virus: Novel Tools for Generation of Molecularly Defined Herpesvirus Vaccines

Abstract: Marek's disease (MD), a highly infectious disease caused by an oncogenic herpesvirus, is one of the few herpesvirus diseases against which live attenuated vaccines are used as the main strategy for control. We have constructed bacterial artificial chromosomes (BACs) of the CVI988 (Rispens) strain of the virus, the most widely used and effective vaccine against MD. Viruses derived from the BAC clones were stable after in vitro and in vivo passages and showed characteristics and growth kinetics similar to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 22 publications
3
49
0
Order By: Relevance
“…Although whether or not REV-LTR insertion affects the in vivo expression of MDV-1-encoded miRNAs is unknown as yet, our research may provide meaningful clues for further evaluating their functions, especially for the twelve miRNAs highlighted in this study. Based on the successful establishment of strategies for mRNA target prediction and experimental identification (Kuhn et al, 2008;Alexiou et al, 2009;Bartel, 2009), and the application of bacterial artificial chromosomes in research on MD pathogenesis (Schumacher et al, 2000;Petherbridge et al, 2003Petherbridge et al, , 2004Sun et al, 2009Sun et al, , 2010, focusing on those miRNAs shown to be expressed in vivo in this study should reveal more about the biological functions of MDV-1-encoded miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Although whether or not REV-LTR insertion affects the in vivo expression of MDV-1-encoded miRNAs is unknown as yet, our research may provide meaningful clues for further evaluating their functions, especially for the twelve miRNAs highlighted in this study. Based on the successful establishment of strategies for mRNA target prediction and experimental identification (Kuhn et al, 2008;Alexiou et al, 2009;Bartel, 2009), and the application of bacterial artificial chromosomes in research on MD pathogenesis (Schumacher et al, 2000;Petherbridge et al, 2003Petherbridge et al, , 2004Sun et al, 2009Sun et al, , 2010, focusing on those miRNAs shown to be expressed in vivo in this study should reveal more about the biological functions of MDV-1-encoded miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The RB-1B strain of MDV isolated in the early 1980s is a highly oncogenic strain (5,6) that consistently induces a high incidence of MD with rapid-onset tumors in visceral organs. We have previously shown that RB-1B infection in 1-week-old Rhode Island red chickens caused a 100% incidence of MD with tumors in visceral organs 6 to 7 weeks after infection (4). Taking advantage of this high oncogenic potential, we have chosen the RB-1B strain for the construction of BAC clones to identify oncogenic determinants of MDV.…”
Section: Marek's Disease Virus (Mdv) Is An Oncogenic Alphaherpesvirusmentioning
confidence: 99%
“…The entire sequence of the putative promoter of the GaHV-2 LAT transcript was amplified from Bacmide DNA of the RB-1B strain (Petherbridge et al 2003). The initial construct extended from nucleotide 142486 to nucleotide 143448 of the reference RB-1B genome (GenBank accession number EF523390), covering the region between the telomeric repeat and the LAT-miRNA cluster.…”
Section: Plasmid Constructsmentioning
confidence: 99%